Moniliformediquinone as a potential therapeutic agent, inactivation of hepatic stellate cell and inhibition of liver fibrosis in vivo. Issue 1 (December 2016) - Tseng, Tsui-Hwa; Lin, Wea-Lung; Chen, Zi-Hui; Lee, Yean-Jang; Shie, Ming-Shiun; Lee, Kam-Fai; Shen, Chien-Heng; Kuo, Hsing-Chun
Abstract Background Moniliformediquinone (MFD), a phenanthradiquinone inDendrobium moniliforme, was synthesized in our laboratory. Beyond its in vitro inhibitory effects on cancer cells, other biological activity of MFD is unknown. The purpose of the present study was to investigate the effects of MFD on hepatic fibrogenesis in vitro and in vivo. Methods Hepatic stellate HSC-T6 was cultured. Cell viability assay and western blot analyses were performed. Male ICR mice were evaluated on CCl4 -induced hepatotoxicity using both histological examination and immunohistochemical staining. Results First, in vitro study showed that the synthesized MFD effectively attenuated the expression of transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF), α-smooth muscle actin (α-SMA), and type I collagen (COL-1), which modulated the hepatic fibrogenesis. Furthermore, MFD reduced the phosphorylation of p65 NFκB in HSC-T6 cells. In vivo, liver fibrosis was induced by CCl4 twice a week for 10 weeks in mice. The administration of the MFD was started after 1 week of CCl4 thrice-weekly; the MFD significantly reduced plasma aspartate transaminase (AST) and lactose dehydrogenase (LDH) as well as hepatic hydroxy-proline, α-SMA, and COL-1 expression in CCl4 -treated mice. Pathological analysis showed that the MFD alleviated CCl4 -induced hepatic inflammation, necrosis and fibrosis. These results suggest that MFD possesses therapeutic potential for liver fibrosis. Conclusions The synthesized MFD exhibits anti-fibrotic potential by inactivation of HSCs in vitro and decreases mouse hepatic fibrosis in vivo. Further investigation into their clinical therapeutic potential is required.